Nuclear Power and Energy Policy - Stoker, Gerry. author. aut Link
XI, 245 p.
Keywords: This book explores how different governments have leveraged their capacity to advance a revival of nuclear power. Presenting in-depth case studies of France, Finland, Britain and the United States, Baker and Stoker argue that governments may struggle to promote new investment in nuclear power.